Follicular environment and oocyte maturation: roles of local peptides and steroids - Buratini, Jose [UNESP]; Silva Soares, Ana Caroline [UNESP]; Barros, Rodrigo Garcia [UNESP] (Brazilian Coll Animal Reproduction, 2017)
A large amount of data on the mechanisms regulating cumulus-oocyte maturation in mammals has been generated in the last 20 years. It has been made clear that oocyte-secreted factors play a central role in the control of cumulus differentiation and oocyte developmental competence. However, more recent data indicate that cumulus-derived factors are also involved. In this mini-review, we have compiled and discussed data produced in our laboratory about the involvement of oocyte and cumulus-derived peptides, including fibroblast growth factors, bone morphogenetic protein 15, Kit ligand and natriuretic peptide C, in the regulation of cumulus metabolism and oocyte nuclear maturation. In addition, we discuss the interaction of follicular steroids with natriuretic peptide C in the control of meiosis progression.
Keywords: oocyte; cumulus cells; intrafollicular peptides; steroids; in vitro maturation; cattle